Comparative Enhancer Map of Cattle Muscle Genome Annotated by ATAC-Seq - Cao, Xiukai; Cheng, Jie; Huang, Yongzhen; Lan, Xianyong; Lei, Chuzhao; Chen, Hong (Frontiers in Veterinary Science, 2021)
Annotating regulatory elements could benefit the interpretation of the molecular mechanism of genome-wide association study (GWAS) hits. In this work, we performed transposase-accessible chromatin with sequencing (ATAC-seq) to annotate the cattle muscle genome’s functional elements. A total of 10,023 and 11,360 peaks were revealed in muscle genomes of adult and embryo cattle, respectively. The two peak sets produced 8,850 differentially accessible regions (DARs), including 2,515 promoters and 4,319 putative enhancers. These functional elements were associated with the cell cycle, muscle development, and lipid metabolism. A total of 15 putative enhancers were selected for a dual-luciferase reporter assay, and 12 of them showed enhancer activity in cattle myoblasts. Interestingly, the GeneHancer database has annotated the interactions of eight active enhancers with gene promoters, such as embryo-specific peak1053 (log2FC = 1.81, embryo/adult, E/A) with ligand-dependent nuclear receptor corepressor-like protein (LCORL) and embryo-specific peak4218 (log2FC = 1.81) with FERM domain-containing 8 (FRMD8). A total of 295 GWAS loci from the animal QTL database were mapped to 183 putative enhancers, including rs109554838 (associated with cattle body weight and average daily gain) to peak1053 and rs110294629 (associated with beef shear force and tenderness score) to peak4218. Notably, peak4218 has been found to be involved in mouse embryo development. Deleting peak4218 clearly reduced luciferase activity (P = 3.30E-04). Our comparative enhancer map is expected to benefit the area of beef cattle breeding.